2002
DOI: 10.1101/gr.226102
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Cot Analysis, DNA Cloning, and High-Throughput Sequencing Facilitates Genome Characterization and Gene Discovery

Abstract: Cot-based sequence discovery represents a powerful means by which both low-copy and repetitive sequences can be selectively and efficiently fractionated, cloned, and characterized. Based upon the results of a Cot analysis, hydroxyapatite chromatography was used to fractionate sorghum (Sorghum bicolor) genomic DNA into highly repetitive (HR), moderately repetitive (MR), and single/low-copy (SL) sequence components that were consequently cloned to produce HRCot, MRCot, and SLCot genomic libraries. Filter hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(158 citation statements)
references
References 65 publications
(79 reference statements)
2
154
0
2
Order By: Relevance
“…However, the Huck element is only a middle-repetitive DNA in S. bicolor (Peterson et al, 2002) and was not seen at all in our sugarcane data set (data not shown). This element is absent from the rice (Oryza sativa) genome, even at an e-value of 1E-01.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the Huck element is only a middle-repetitive DNA in S. bicolor (Peterson et al, 2002) and was not seen at all in our sugarcane data set (data not shown). This element is absent from the rice (Oryza sativa) genome, even at an e-value of 1E-01.…”
Section: Resultsmentioning
confidence: 88%
“…This element is absent from the rice (Oryza sativa) genome, even at an e-value of 1E-01. Leviathan is a shared most abundant family among the S. propinquum and Saccharum species, but has a much lower copy number in S. bicolor (Peterson et al, 2002). Leviathan is a middle-repetitive DNA in B73 maize, but none of the element is intact (that is, with two alignable LTRs), so this TE has not been active for a very long time, and thus was missed with the intact element discovery pipeline applied by Baucom et al (2009).…”
Section: Resultsmentioning
confidence: 99%
“…Four LTRretrotransposon families (Ji, Opie, Huck, and Zeon-1) account for 32% of the Ϸ2,500-Mb maize genome (22), and one family (IRRE) accounts for Ϸ10% of the Ϸ10,000-Mb genome of Iris brevicaulis (37). Even the relatively small sorghum genome (Ϸ700 Mb) contains a high copy number retrotransposon family (Retrosor6, Ϸ6,000-7,000 copies) that accounts for Ϸ6% of the genome (38). In contrast, massive amplification of one or more retrotransposon family has not occurred in B. oleracea; the most abundant family contains only Ϸ140 copies (BoCP IXc).…”
Section: Discussionmentioning
confidence: 99%
“…In regions of the maize genome with lower gene density, comparative gene-island sequencing would be even more efficient. Highthroughput sequencing strategies are currently under development that selectively target gene-rich, low-copy, hypomethylated regions of the genome (Rabinowicz et al, 1999;Peterson et al, 2002). Because the gene-island sequencing method can be tar-geted to genomic regions of special interest or low representation, it should be a useful complementary approach to genome-wide sequencing projects.…”
Section: Comparative Sequence Analysis By Gene-island Sequencingmentioning
confidence: 99%